2004
DOI: 10.1103/physreve.70.056215
|View full text |Cite
|
Sign up to set email alerts
|

Scattering off two oscillating disks: Dilute chaos

Abstract: We investigate the role of the unstable periodic orbits and their manifolds in the dynamics of a time-dependent two-dimensional scattering system. As a prototype we use two oscillating disks on the plane with the oscillation axes forming an angle theta. The phase space of the system is five dimensional and it possesses a variety of families of unstable periodic orbits (UPOs) with intersecting manifolds. We perform numerical experiments to probe the structure of distinct scattering functions, in one and two dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Note that the sense of precession is inverted under time reversal t → −t (keeping B → B), revealing the time arrow inherent in (5). (3,4). In each of the two sectors 1 and 2, the field is isotropic, with an angle of π/2 between the two sectors.…”
Section: Equations Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the sense of precession is inverted under time reversal t → −t (keeping B → B), revealing the time arrow inherent in (5). (3,4). In each of the two sectors 1 and 2, the field is isotropic, with an angle of π/2 between the two sectors.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…The field configuration defined in (3,4) implies that within the intervals [−a, 0] and [0, a], the field varies only in magnitude but not in direction. This allows for further simplifications.…”
Section: Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been found that complex behavior with different characteristics can be observed in scattering systems involving a time-dependent scattering potential [23,24,25,26,27,28,29]. As a representative example of such a system the scattering of freely moving, non-interacting particles off two hard, infinitely heavy, oscillating discs on the plane has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[25] the term dilute chaos was introduced to describe the behavior characterized by the accumulation of peaks, associated with processes leading to maximum energy exchange between scattered particles and an oscillating target around the position of the UPOs of the system. The set of the observed peaks possesses a self-similar structure either in an approximative sense occurring only between two scales determined by the geometry of the particular setup [24] or in a local sense in the neighborhood of specific isolated points in phase space [25]. The significant role of processes with maximum energy exchange in the scattering off a time-dependent hard potential becomes more transparent in the case of scattering off a single oscillating disc [26].…”
Section: Introductionmentioning
confidence: 99%